PENGARUH SELF EFFICACY, COMPETENCY TERHADAP QUALITY OF WORK LIFE DAN WORK ENGAGEMENT (Pada ASN Milenial BPSDM Kementerian Hukum dan HAM) - Welliam Bergen, (2020)
The purpose of this quantitative research that aim to determine the influence of self efficacy and competence of quality of work life and work engagement. The millenial employees of BPSDM Ministry of Law and Human Rights became the population in this study. The number of samples used in this study was 126 respondents, using the simple random sampling method. Data is collected by distributing questionnaires. The analysis technique used is Structure Equation Models (SEM) with Partial Least Square (PLS). The result of this study indicate (1) Self efficacy has not effect on work engagement with a path coefficient of 0,129. (2) Competency has an effect on work engagement with a path coefficient of 0,045. (3) Self efficacy has not effect on quality of work life with a path coefficient of 0,133. (4) Competency has an effect on quality of work life with a path coefficient of 0,442. (5) Quality of work life has an effect on work engagement with a path coefficient of 0,639.